Metadata for information management and retrieval understanding metadata and its use - Haynes, David (London Facet Publishing, 2018)
"Metadata for Information Management and Retrieval has been fully revised to bring it up to date with new technologies and standards. It builds on the concept of metadata through an exploration of its purposes and uses as well as considering the main aspects of metadata management. This new edition, containing new chapters on 'Very Large Data Collections' and the 'Politics and Ethics of Metadata', assesses the current theory and practice of metadata and examines key developments in terms of both policy and technology. Coverage includes: defining, describing and expressing metadata, data modelling, metadata and information retrieval, big data, linked data, and social media, research data collections and open data repositories, metadata in information governance: compliance, risk and information security, managing intellectual property rights, [and] the politics of metadata: ethics, power and money"--Publisher's website.
Includes bibliographical references (pages 239-256) and index.
Keywords: Information retrieval; Big data; Intellectual property; Intellectual property -- Law and legislation; Information storage and retrieval; Metadata; Information organization